Deep Learning applied to the Identification of Fruit Fly in Intelligent Traps - Martins, Valter; Freitas, Lucas; Brisolara, Lisane; de Aguiar, Marilton; Ferreira Jr., Paulo Roberto (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2019)
This paper presents a novel approach to the identification of two species of fruit flies as part of a network of intelligent traps designed to monitor these insects population in a plantation. This identification is done essentially by a convolutional neural network which learns the characteristics of the insects based on its images made from the adhesive floor of the trap. The proposed approach also uses a simple image digital processing technique to prepare the image and a perceptron neural network to classify the objects into the right class given its characteristics. We have trained several convolutional neural network architectures, with different configurations, trough a dateset of images collected on the field. Our aim was to find the one with high precision and low time needed to the classification. The best performance was achieved by ResNet18, with a precision of 93.55% and 91.28%. for the classification of the fruit flies focusing here, named Ceratitis Capitata and Grapholita Molesta, respectively. As it is required that the classification occurs embedded on the trap, despite our efforts, the only architecture that have ran in our platform was the SqueezeNet. We show that its precision is 88.56% and 90.60%, for the classification of Ceratitis Capitata and Grapholita Molesta, respectively, which is very close to the best performance one. According our expert partners, the results are feasible to a real-world application.